Advances in Screening and Development of Therapeutic Aptamers Against Cancer Cells - Li, Zheng; Fu, Xuekun; Huang, Jie; Zeng, Peiyuan; Huang, Yuhong; Chen, Xinxin; Liang, Chao (Frontiers in Cell and Developmental Biology, 2021)
Abstract Cancer has become the leading cause of death in recent years. As great advances in medical treatment, emerging therapies of various cancers have been developed. Current treatments include surgery, radiotherapy, chemotherapy, immunotherapy, and targeted therapy. Aptamers are synthetic ssDNA or RNA. They can bind tightly to target molecules due to their unique tertiary structure. It is easy for aptamers to be screened, synthesized, programmed, and chemically modified. Aptamers are emerging targeted drugs that hold great potentials, called therapeutic aptamers. There are few types of therapeutic aptamers that have already been approved by the FDA for disease treatment. Now more and more therapeutic aptamers are in the stage of preclinical research or clinical trials. This review summarized the screening and development of therapeutic aptamers against different types of cancer cells.